Pulse Dose Corticosteroid Therapy in Vitiligo: A Narrative Literature Review - Elok Nurfaiqoh; Arie Kusumawardani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Vitiligo is an idiopathic skin depigmentation disorder with clinical symptoms of macules and depigmented patches on the skin. Vitiligo is a multifactorial disorder associated with genetic and non-genetic. There are two types of vitiligo: non-segmental and segmental vitiligo. The type of vitiligo can be determined based on physical examination and affects the disease course, prognosis, and therapy response. Vitiligo management is still a challenge on its own because the etiology is not clear, and many factors must be considered in the vitiligo treatment. Vitiligo management greatly varies depending on the activity and the disease expansion. The goals of vitiligo treatment include stopping disease progression, increasing repigmentation, and preventing recurrence. Vitiligo therapy options vary widely, but none have been effective in treating vitiligo with a high recurrence rate. One of the vitiligo treatment options is systemic corticosteroids given in pulse doses bringing the effect of decreasing the vitiligo progression and minimizing side effects. This literature review aims to determine the use of pulse dose corticosteroid therapy in vitiligo.